Validity and reliability of the Turkish version of the Visual Analog Sleep Scale - Çetinkaya, Funda; Karabulut, Nezihe (Kontakt (České Budějovice), 2016)
Objectives: The aim of this study was to adapt the English version of the Visual Analog Sleep Scale (VAS Scale) to Turkish, and to assess the validity and reliability of this Turkish version. Material and methods: The study design was both descriptive and methodological. The study group was comprised of 75 patients, who agreed to participate in the study. Each had received total hip replacement surgery in an orthopedic clinical hospital. Data was collected using a Turkish translation of the VAS Scale. Psychometric testing of the adapted instrument was carried out to establish internal consistency, interim correlation, and construct validity. The Kaiser-Meyer-Olkin and Barlett’s tests were applied to determine the sampling adequacy and suitability to the factor analysis. Results: The Kaiser-Meyer-Olkin value was found to be 0.89, and this value indicates suitability for principal component analysis. Similarly, Barlett’s test results (X2 = 608.74, p = 0.000) also indicate the interrelationships of the data and suitability for the factor analysis. The eigenvalue of the VAS Scale reduced to 10 items was found to be 6.65 and the variance was 66.52. The VAS Scale Cronbach’s alpha was 0.82 for the test items. The test-retest stability coefficient (validity of the scale) was 0.92. Alpha coefficient was found to be 0.94 for internal consistency. Conclusion: The original VAS Scale consisted of three sub-scales and 15 items, whereas the Turkish version has one dimension and 10 items. The Turkish version of the VAS Scale adapted to the orthopedics clinic can be used as a one-factor tool.
Keywords: Visual Analog Scale; Sleep Wake Disorders; Reproducibility of Results; Turecko; statistika jako téma; vizuální analogová stupnice; lidé; Statistics as Topic; Turkey; Humans; reprodukovatelnost výsledků; poruchy spánku a bdění